UV-induced inhibition of transcription involves repression of transcription initiation and phosphorylation of RNA polymerase II - Rockx, Davy A. P. (The National Academy of Sciences, 2000)
Cells from patients with Cockayne syndrome (CS) are hypersensitive to DNA-damaging agents and are unable to restore damage-inhibited RNA synthesis. On the basis of repair kinetics of different types of lesions in transcriptionally active genes, we hypothesized previously that impaired transcription in CS cells is a consequence of defective transcription initiation after DNA damage induction. Here, we investigated the effect of UV irradiation on transcription by using an in vitro transcription system that allowed uncoupling of initiation from elongation events. Nuclear extracts prepared from UV-irradiated or mock-treated normal human and CS cells were assayed for transcription activity on an undamaged β-globin template. Transcription activity in nuclear extracts closely mimicked kinetics of transcription in intact cells: extracts from normal cells prepared 1 h after UV exposure showed a strongly reduced activity, whereas transcription activity was fully restored in extracts prepared 6 h after treatment. Extracts from CS cells exhibited reduced transcription activity at any time after UV exposure. Reduced transcription activity in extracts coincided with a strong reduction of RNA polymerase II (RNAPII) containing hypophosphorylated C-terminal domain, the form of RNAPII known to be recruited to the initiation complex. These results suggest that inhibition of transcription after UV irradiation is at least partially caused by repression of transcription initiation and not solely by blocked elongation at sites of lesions. Generation of hypophosphorylated RNAPII after DNA damage appears to play a crucial role in restoration of transcription. CS proteins may be required for this process in a yet unknown way.